Who took my shoe? - Emigh, Karen; Dana, Steve (Arlington, Tex. : Future Horizons, 2003)
An autistic boy named Brett struggles with the questions "who", "what", "when", "where", "why" and "how" when he loses his shoe.
Keywords: Autism -- Fiction; Lost and found possessions -- Fiction; Autistic children -- Fiction; Special needs -- Fiction